Towards optimal control of concentric tube robots in stereotactic neurosurgery. Issue 6 (2nd November 2019) - Flaßkamp, K.; Worthmann, K.; Mühlenhoff, J.; Greiner-Petter, C.; Büskens, C.; Oertel, J.; Keiner, D.; Sattel, T.
ABSTRACT: We consider the design and control problem of concentric tubes used in stereotactic neurosurgery. The goal is to optimally reach a configuration of the cannula linking an entry point on the skullcap to a pre-specified region inside the brain. Key issues related to this task are the mechanical behaviour of the cannula and the topography of the brain. We formulate an optimal control problem in order to determine a feasible path while minimizing brain damage caused by missing follow-the-leader behaviour. Numerical results show the potential of the proposed approach.